Apoptosis-inducing effect of Artonin E in breast cancer - Abdul Kadir, Arifah; Etti, Imaobong Christopher; Abdullah, Rasedee @ Mat (IntechOpen, 2018)
Breast cancer is among the principal cause of cancer fatalities in women. Notwithstanding the use of chemotherapy and advances in drug delivery techniques, cancer-related morbidity and mortality are still increasing with the increase in resistance to known therapeutics. This dilemma has drastically reduced the rate of survival from this deadly disease, creating a dire need for new drugs, especially from natural sources that would exhibit similar or better anticancer properties while imparting minimal adverse side effects. Among the bewildering hallmark capabilities of cancer is the evasion of apoptosis while in its course to immortality. Thus, induction of apoptosis in cancerous cells is an important breakthrough that cannot be ignored. There are, however, two major pathways of apoptosis in mammals, viz., the death receptor–mediated pathway (extrinsic pathway) and the mitochondrial-mediated pathway (intrinsic pathway). Artonin E, a prenylated flavonoid isolated from the stem bark of Artocarpus elasticus, was seen to induce apoptosis in MCF-7 breast cancer cells, hence halting the breast cancer cells in their journey to immortality.